-18-6k=6(13k)

Simple and best practice solution for -18-6k=6(13k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18-6k=6(13k) equation:


Simplifying
-18 + -6k = 6(13k)

Remove parenthesis around (13k)
-18 + -6k = 6 * 13k

Multiply 6 * 13
-18 + -6k = 78k

Solving
-18 + -6k = 78k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-78k' to each side of the equation.
-18 + -6k + -78k = 78k + -78k

Combine like terms: -6k + -78k = -84k
-18 + -84k = 78k + -78k

Combine like terms: 78k + -78k = 0
-18 + -84k = 0

Add '18' to each side of the equation.
-18 + 18 + -84k = 0 + 18

Combine like terms: -18 + 18 = 0
0 + -84k = 0 + 18
-84k = 0 + 18

Combine like terms: 0 + 18 = 18
-84k = 18

Divide each side by '-84'.
k = -0.2142857143

Simplifying
k = -0.2142857143

See similar equations:

| 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 | | 3(x+1)+7(x+1)-6= | | 8x=8x+6 | | 0.5(x+4)-(10x+9)=-77 | | -4(1x+10)=-32 | | 25+15=x | | .33(3x+6)=8x+10 | | -6=-5x+6 | | 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x |

Equations solver categories